Long-life anti-micro-pitting industrial gear oil and preparation method thereof

By using the combination of nanodiamond and polymethacrylate in industrial gear oil, the problem of insufficient anti-micropilot and water separation performance in mining machinery is solved, and a longer service life and higher performance stability are achieved.

CN119552698APending Publication Date: 2025-03-04DONGGUAN PACIFIC BOGAO LCBRICANT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411622560.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Traditional industrial gear oil is difficult to maintain lubrication and anti-emulsification functions for a long time in mining machinery applications, resulting in serious micropitting and affecting the service life of the gears.

Method used

Polyα-olefin base oil, ester oil, alkyl phosphite, phosphorodithioate, nanodiamond, polymethacrylate and other components are used to form composite materials through the interface interaction between nanodiamond and polymethacrylate, thereby improving the anti-micropied corrosion and water separation properties of the oil.

Benefits of technology

It significantly improves the micro-pitting and water separation performance of industrial gear oil, extends the service life of gears, reduces wear and corrosion risks, and meets the high performance needs of mining machinery in high load and humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133828680000131
    Figure BDA0005133828680000131
  • Figure BDA0005133828680000132
    Figure BDA0005133828680000132
  • Figure BDA0005133828680000141
    Figure BDA0005133828680000141
Patent Text Reader

Abstract

The invention relates to the technical field of gear oil, and discloses long-life micro-pitting-resistant industrial gear oil. The lubricating oil comprises the following components in parts by weight: 50-70 parts of ester oil, 10-20 parts of alkyl phosphite, 2-5 parts of dithiophosphate, 2-8 parts of a nano material, 1-3 parts of a phenolic antioxidant, 1-2 parts of an amine antioxidant, 1-2 parts of a benzotriazole preservative, 1-3 parts of fatty alcohol, 5-10 parts of polymethacrylate and 2-5 parts of a viscosity index improver, the industrial gear oil provided by the invention greatly overcomes the defects that when common industrial gear oil is applied to mining machinery, the micro pitting corrosion resistance is poor, the water diversion performance is poor, and the micro pitting corrosion phenomenon is further aggravated due to poor emulsion resistance. The high requirements of mining machinery on the performances such as micro pitting corrosion resistance of the gear oil in a humid and complex high-load operation environment are met, and the service life of an industrial gear of the mining machinery is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gear oils and relates to a long-life anti-micropitting industrial gear oil and a preparation method thereof. Background Art

[0002] Industrial gear oil, as an indispensable lubricating medium in mechanical transmission systems, undertakes multiple key functions. It can not only effectively reduce friction and wear and extend the service life of equipment, but also reduce the operating temperature by cooling components to prevent overheating. In addition, industrial gear oil also provides the necessary buffering and anti-vibration effects to ensure the stability and reliability of mechanical equipment under high-load operation.

[0003] Industrial gear lubricants are widely used in the field of heavy-duty machinery, especially in mining machinery, where the application of industrial gear oil is particularly critical. Mining machinery is often subjected to extremely high gear contact stress, which can reach 400 to 1000 MPa. Under such a high-pressure environment, the relative movement between the two tooth surfaces during the gear meshing process and the combined effects of contact stress and shear stress will cause the local temperature to rise sharply. High temperature will not only cause the oil film to rupture or the chemical reaction film to fail, but also cause complex elastic-plastic deformation. These deformations ultimately lead to the transfer and loss of tooth surface material, forming tiny cracks and pits, and producing micro-pitting.

[0004] In addition, there is often a large amount of water in the mining environment. In addition to accelerating the rust and corrosion of metal parts, this water is easily mixed into the gear oil, causing the oil to emulsify, destroying the stability of the oil film, making the oil film thinner or broken, reducing the lubrication effect, causing direct contact between the tooth surfaces, and aggravating wear and pitting.

[0005] Therefore, in order to ensure the normal operation and extended service life of mining machinery gears, it is very important to provide a long-life anti-micropitting industrial gear oil. Summary of the invention

[0006] In view of the problem in the prior art that traditional industrial gear oil is difficult to effectively maintain its lubrication and anti-emulsification functions for a long time when used in mining machinery, the present invention provides an industrial gear oil with a longer service life and the ability to effectively resist micropitting and a preparation process thereof.

[0007] The first object of the present invention is to provide a long-life anti-micropitting industrial gear oil.

[0008] A long-life anti-micropitting industrial gear oil, calculated by weight, comprises the following components:

[0009] Poly-alpha-olefin base oil: 50-70 parts;

[0010] Ester oil: 10-20 parts;

[0011] Alkyl phosphite: 5-10 parts;

[0012] Phosphorodithioate: 2-5 parts;

[0013] Nanomaterials: 2 to 8 parts;

[0014] Phenolic antioxidants: 1-3 parts;

[0015] Amine antioxidant: 1-2 parts;

[0016] Benzotriazole preservatives: 1-2 parts;

[0017] Fatty alcohol: 1-3 parts;

[0018] Polymethacrylate: 5-10 parts;

[0019] Viscosity index improver: 2 to 5 parts.

[0020] Preferably, the nano material includes nano diamond, and the particle size of the nano diamond is 20-50 nm. Nano diamonds within this particle size range can exhibit excellent effects in the gear oil system.

[0021] Nanodiamond, as a one-dimensional carbon nanomaterial, has excellent mechanical strength and hardness. The main function of polymethacrylate (PMA) in industrial lubricants is to improve the low temperature performance and viscosity-temperature performance of the oil, and to improve the adaptability and shear stability of the base oil. During the process of formula development, the inventor accidentally discovered that when nanodiamond and polymethacrylate are present in the formula at the same time, the anti-micropitting performance of industrial gear oil is significantly better than that of industrial gear oil with a single component of nanodiamond or polymethacrylate, and the industrial gear oil at this time has a certain water separation performance.

[0022] It is speculated that the internal reason may be that when nanodiamonds and PMA coexist by stirring and dispersion, the interface interaction and mechanical interlocking between nanodiamonds and PMA matrix increase the Young's modulus and yield stress of the composite material, thereby affecting the overall mechanical properties of the composite material.

[0023] In industrial gear oil, nanodiamonds connected by interfacial forces can fill the microscopic pits on the metal surface to form a hard protective film, thereby reducing direct contact and wear between metals. Combined with PMA as a high molecular polymer, it has good lubricity and adhesion, and can form a uniform lubricating film on the metal surface, further reducing the friction coefficient and wear rate.

[0024] At the same time, nanodiamonds also have a certain self-repairing ability. Under the high load of mining machinery, nanodiamond particles may fall off from the matrix and re-embed into new pits, thereby achieving self-repair. This self-repairing ability helps to extend the service life of gear oil and maintain its lubrication performance.

[0025] Regarding water separation, under the action of nanodiamond interfacial forces, the functional groups in the molecular structure of PMA show the ability to adsorb on the oil-water interface, thereby reducing the interfacial tension between oil and water, separating water droplets from oil, and thus improving the water separation of the oil; or the synergy between nanodiamonds and PMA changes the properties of the interfacial film, making it unstable, promoting the aggregation and sedimentation of water droplets, and ultimately achieving oil-water separation.

[0026] Preferably, the nanodiamond is nanodiamond modified by a silane coupling agent.

[0027] Specifically, the silane coupling agent used for modifying nanodiamonds is silane coupling agent A151. The specific modification method is as follows: dissolve silane coupling agent A151 in a mixed solution of alcohol and water, and stir thoroughly to form a uniform solution. The concentration range of the silane coupling agent is controlled between 2% and 5%. Then, the nanodiamond is added to the above solution, and stirring is continued for 6 to 8 hours to ensure that the nanodiamond is fully in contact with the silane coupling agent A151, so that the silane coupling agent A151 reacts chemically with the functional groups on the surface of the nanodiamond to achieve chemical bonding. After the reaction is completed, the nanodiamond is washed with anhydrous ethanol to remove unreacted silane coupling agent A151 and other impurities. Finally, the washed nanodiamond is vacuum dried at a temperature of 55 to 65°C for 20 to 30 hours to obtain a modified nanodiamond powder.

[0028] The modified nanodiamond has higher dispersibility and compatibility in the system, and can better interact with the metal surface to form a tough lubricating film. This lubricating film can significantly reduce the friction coefficient between metals and reduce wear, which can further increase the service life of gears or equipment in a macroscopic way.

[0029] Preferably, the nanomaterial further comprises nanocopper, and the weight ratio of the nanodiamond to the nanocopper is 1:1.2 to 1.5. In some preferred embodiments, the weight ratio of the nanodiamond to the nanocopper may be 1:1.2, 1:1.3, 1:1.4, or 1:1.5.

[0030] When studying the role of nanomaterials in the system, the inventors tried a variety of other nanomaterials. However, these materials either reduced the anti-micropitting effect or had poor anti-wear performance. In an unexpected experiment, the inventors found that when all were replaced with nano-copper, although the anti-wear performance was not as good as nano-diamond, it had significant water separation and anti-emulsification properties. Based on this discovery, the inventors further explored and modified nano-copper to improve its performance in gear oil, especially the anti-micropitting performance to further increase the life of the gear oil.

[0031] Preferably, the nano copper is nano copper modified by organic quaternary ammonium salt.

[0032] Preferably, the organic quaternary ammonium salt is octadecyltrimethylammonium chloride.

[0033] The nano copper was modified by using octadecyltrimethylammonium chloride to improve its performance in industrial gear oil.

[0034] Preferably, the modification method of nano copper comprises the following steps:

[0035] Step 1: Accurately weigh appropriate amounts of Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride, dissolve them in distilled water, and stir them thoroughly to form a uniform first solution and a second solution;

[0036] Step 2: Add the first solution dropwise into the second solution, continue to stir thoroughly, and obtain a suspension;

[0037] During this process, the octadecyltrimethylammonium chloride molecular chain enters the surface structure of nanocopper through ion exchange reaction.

[0038] Step 3: After the suspension is loaded into the PPL liner, it is placed in a hydrothermal synthesis kettle made of stainless steel; the hydrothermal synthesis kettle is placed in an oven and heated to 95-105° C. for 20-30 hours to complete the preparation of doped modified nano copper.

[0039] Step 4: After the hydrothermal synthesis reactor is cooled naturally, the supernatant is removed, and the precipitate is washed with deionized water for 2 to 3 times, and then centrifuged after ultrasonic treatment to obtain a precipitate. Then, the precipitate is washed with anhydrous ethanol, and then centrifuged after ultrasonic treatment to obtain a white precipitate;

[0040] Step 5: vacuum drying the white precipitate at 55-65°C for 20-30 hours to obtain a yellow powder;

[0041] Step 6: calcine the yellow powder at 380-420° C. for 3-5 hours under N2 atmosphere to obtain modified nano copper.

[0042] Preferably, in the modification step, the mass ratio of the Cu(NO3)2·3H2O to the octadecyltrimethylammonium chloride is 1:1.8-2.2. In some specific embodiments, the mass ratio of Cu(NO3)2·3H2O to octadecyltrimethylammonium chloride can be 1:1.8, 1:1.9, 1:2.0, 1:2.1, or 1:2.2.

[0043] In a preferred embodiment, in the modification step, the mass ratio of the Cu(NO3)2·3H2O to the octadecyltrimethylammonium chloride is 1:2.

[0044] Octadecyl trimethyl ammonium chloride modifies the surface of nano copper through ion exchange reaction, changing the originally hydrophilic surface into hydrophobic surface, which makes nano copper easier to disperse in non-polar media, thereby improving the dispersibility in the gear oil matrix. The adsorption behavior of octadecyl trimethyl ammonium chloride on the surface of nano copper is mainly manifested as electrostatic force, which enhances the surface charge density and zeta potential of nano copper and improves the dispersion stability in gear oil.

[0045] The modified nano-copper can form a protective film on the metal surface, effectively reducing friction and wear, and has improved anti-wear performance compared to unmodified nano-copper materials. Although octadecyl trimethyl ammonium chloride itself is not a metal, nano-copper modified with octadecyl trimethyl ammonium chloride may simulate the micro-bearing effect to a certain extent and further improve anti-wear performance.

[0046] When water is mixed into the gear oil, both free water and dissolved water will affect micropitting. Free water will accelerate the oxidation and deterioration of the lubricating oil, while dissolved water will change the properties of the lubricating oil, reduce viscosity and extreme pressure wear resistance, thereby aggravating the occurrence of micropitting; and the presence of water will accelerate the rust and corruption of gears, affecting the life of gears. The modified nano-copper particles can form a stable film at the interface between gear oil and water, preventing oil-water emulsification and improving the stability of the interface. As the alkyl chain of the modified nano-copper increases, the hydrophobicity of the surface gradually increases, improving the water separation performance of the gear oil, making it difficult for water to combine with nano-copper to form an emulsion, making it easier to separate oil and water. Reduce the formation of emulsions after oil and water are mixed, resulting in the obstruction of the formation of lubricating film, increasing the risk of wear and scratches on the gear surface, and avoiding the emulsion accelerating the oxidation and deterioration of oil products, reducing the anti-wear performance of gear oil.

[0047] The second object of the present invention is to provide a method for preparing a long-life micropitting-resistant industrial gear oil.

[0048] A method for preparing a long-life micropitting-resistant industrial gear oil comprises the following steps:

[0049] S1: Mix 50-70 parts of poly-alpha-olefin base oil and 10-20 parts of ester oil, heat to 50-60°C and maintain, stirring until the mixture is uniform;

[0050] S2: After lowering the temperature to 40-50°C, 5-10 parts of alkyl phosphite, 2-5 parts of dithiophosphate and 2-8 parts of nanomaterial are added in sequence, and stirring is continued for 1-2 hours to ensure that the components are fully dispersed;

[0051] S3: further cooling to 30-40°C, adding 1-3 parts of phenolic antioxidant, 1-2 parts of amine antioxidant and 1-2 parts of benzotriazole preservative in sequence, and stirring for 30 minutes;

[0052] S4: Raise the temperature to 50-60°C again, add 1-3 parts of fatty alcohol, 5-10 parts of polymethacrylate and 2-5 parts of viscosity index improver, and continue stirring for 1 hour;

[0053] S5: Cool naturally to room temperature to produce long-life anti-micropitting industrial gear oil.

[0054] Beneficial effects: The industrial gear oil provided by the present invention greatly overcomes the defects of ordinary industrial gear oil when used in mining machinery, such as poor anti-micropitting performance, poor water separation performance and poor anti-emulsification performance, which further aggravates the micropitting phenomenon. It meets the high requirements of mining machinery in humid and complex environments and high-load operating environments for gear oil anti-micropitting and other properties, and greatly extends the service life of industrial gears of mining machinery. DETAILED DESCRIPTION

[0055] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] The raw materials used in the embodiments of the present invention can all be purchased directly from the market.

[0057] The nano-diamonds in the embodiments of the present invention all have a particle size of 20 to 50 nm.

[0058] The ester oil in the formulation of the present invention is preferably a saturated polyol ester, such as PRIOLUBE3970 and PRIOLUBE3987, both of which are from CRODA (Croda) Company of the United Kingdom.

[0059] The viscosity index improver of the present invention may be Viscotech 6540, Viscotech 6545 or Viscotech 6550, all of which are from BRB (Bib) Company of the Netherlands.

[0060] The modification method of the modified nanodiamond used in the embodiment of the present invention is as follows:

[0061] The silane coupling agent used for modifying nanodiamond is silane coupling agent A151. The specific modification method is as follows: dissolve silane coupling agent A151 in a mixed solution of alcohol and water, and stir it thoroughly to form a uniform solution. The concentration range of the silane coupling agent is controlled between 2% and 5%.

[0062] Then, the nanodiamond is added to the above solution and stirred for 6 to 8 hours to ensure that the nanodiamond is fully in contact with the silane coupling agent A151, so that the silane coupling agent A151 reacts chemically with the functional groups on the surface of the nanodiamond to achieve chemical bonding. After the reaction is completed, the nanodiamond is washed with anhydrous ethanol to remove unreacted silane coupling agent A151 and other impurities. Finally, the washed nanodiamond is vacuum dried at a temperature of 55 to 65°C for 20 to 30 hours to obtain a modified nanodiamond powder.

[0063] The modification method of the modified nano-copper used in the embodiment of the present invention is as follows, and three preparation examples of modified nano-copper are prepared according to different weight proportions of Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride.

[0064] Nano copper preparation example 1

[0065] Step 1: Accurately weigh appropriate amounts of Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride, with the mass ratio of Cu(NO3)2·3H2O to octadecyltrimethylammonium chloride being 1:1.8. Dissolve Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride in distilled water respectively, and stir thoroughly to form a uniform first solution and a second solution;

[0066] Step 2: Add the first solution dropwise into the second solution, continue to stir thoroughly, and obtain a suspension;

[0067] During this process, the octadecyltrimethylammonium chloride molecular chain enters the surface structure of nanocopper through ion exchange reaction.

[0068] Step 3: After the suspension is loaded into the PPL liner, it is placed in a hydrothermal synthesis kettle made of stainless steel; the hydrothermal synthesis kettle is placed in an oven and heated to 95-105° C. for 20-30 hours to complete the preparation of doped modified nano copper.

[0069] Step 4: After the hydrothermal synthesis reactor is cooled naturally, the supernatant is removed, and the precipitate is washed with deionized water for 2 to 3 times, and then centrifuged after ultrasonic treatment to obtain a precipitate. Then, the precipitate is washed with anhydrous ethanol, and then centrifuged after ultrasonic treatment to obtain a white precipitate;

[0070] Step 5: vacuum drying the white precipitate at 55-65°C for 20-30 hours to obtain a yellow powder;

[0071] Step 6: calcine the yellow powder at 380-420° C. for 3-5 hours under N2 atmosphere to obtain modified nano copper.

[0072] Nano copper preparation example 2

[0073] The difference between this preparation example and nano copper preparation example 1 is that the mass ratio of Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride in this preparation example is different. The mass ratio of Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride in this preparation example is 1:2.

[0074] Nano copper preparation example 3

[0075] The difference between this preparation example and nano copper preparation example 1 is that the mass ratio of Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride in this preparation example is different. The mass ratio of Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride in this preparation example is 1:2.2.

[0076] Example 1

[0077] The long-life anti-micropitting industrial gear oil prepared in Example 1 has the following formula and dosage:

[0078] 50 parts of poly-α-olefin base oil, 16 parts of ester oil, 5 parts of alkyl phosphite, 2 parts of dithiophosphate, 8 parts of modified nanodiamond, 1 part of phenolic antioxidant, 2 parts of amine antioxidant, 1 part of benzotriazole preservative, 3 parts of fatty alcohol, 8 parts of polymethacrylate, and 4 parts of viscosity index improver.

[0079] The specific preparation method comprises the following steps:

[0080] S1: Mix the poly-α-olefin base oil and the ester oil, heat to 50-60°C and maintain the temperature, and stir until the mixture is uniform;

[0081] S2: After lowering the temperature to 40-50°C, alkyl phosphite, dithiophosphate and modified nanodiamond are added in sequence, and stirring is continued for 1 hour to ensure that the components are fully dispersed;

[0082] S3: further cooling to 30-40°C, adding phenolic antioxidant, amine antioxidant and benzotriazole preservative in sequence, and stirring for 30 minutes;

[0083] S4: Raise the temperature to 50-60°C again, add fatty alcohol, polymethacrylate and viscosity index improver, and continue stirring for 1 hour;

[0084] S5: Cool naturally to room temperature to produce long-life anti-micropitting industrial gear oil.

[0085] Example 2

[0086] The difference between Example 2 and Example 1 is that the weight parts of the components in the formula of Example 2 are different.

[0087] The long-life anti-micropitting industrial gear oil prepared in Example 2 has the following formula and dosage:

[0088] 60 parts of poly-α-olefin base oil, 20 parts of ester oil, 8 parts of alkyl phosphite, 3 parts of dithiophosphate, 2 parts of modified nanodiamond, 2 parts of phenolic antioxidant, 2 parts of amine antioxidant, 1 part of benzotriazole preservative, 1 part of fatty alcohol, 2 parts of polymethacrylate, and 3 parts of viscosity index improver.

[0089] The specific preparation method comprises the following steps:

[0090] S1: Mix the poly-α-olefin base oil and the ester oil, heat to 50-60°C and maintain the temperature, and stir until the mixture is uniform;

[0091] S2: After lowering the temperature to 40-50°C, alkyl phosphite, dithiophosphate and modified nanodiamond are added in sequence, and stirring is continued for 1 hour to ensure that the components are fully dispersed;

[0092] S3: further cooling to 30-40°C, adding phenolic antioxidant, amine antioxidant and benzotriazole preservative in sequence, and stirring for 30 minutes;

[0093] S4: Raise the temperature to 50-60°C again, add fatty alcohol, polymethacrylate and viscosity index improver, and continue stirring for 1 hour;

[0094] S5: Cool naturally to room temperature to produce long-life anti-micropitting industrial gear oil.

[0095] Example 3

[0096] The difference between Example 3 and Example 1 is that the weight parts of the components in the formula of Example 2 are different.

[0097] The long-life anti-micropitting industrial gear oil prepared in Example 3 has the following formula and dosage:

[0098] 70 parts of poly-α-olefin base oil, 10 parts of ester oil, 10 parts of alkyl phosphite, 5 parts of dithiophosphate, 6 parts of modified nanodiamond, 3 parts of phenolic antioxidant, 1 part of amine antioxidant, 1 part of benzotriazole preservative, 2 parts of fatty alcohol, 10 parts of polymethacrylate, and 2 parts of viscosity index improver.

[0099] The specific preparation method comprises the following steps:

[0100] S1: Mix the poly-α-olefin base oil and the ester oil, heat to 50-60°C and maintain the temperature, and stir until the mixture is uniform;

[0101] S2: After lowering the temperature to 40-50°C, alkyl phosphite, dithiophosphate and modified nanodiamond are added in sequence, and stirring is continued for 1 hour to ensure that the components are fully dispersed;

[0102] S3: further cooling to 30-40°C, adding phenolic antioxidant, amine antioxidant and benzotriazole preservative in sequence, and stirring for 30 minutes;

[0103] S4: Raise the temperature to 50-60°C again, add fatty alcohol, polymethacrylate and viscosity index improver, and continue stirring for 1 hour;

[0104] S5: Cool naturally to room temperature to produce long-life anti-micropitting industrial gear oil.

[0105] Example 4

[0106] The difference between this embodiment and embodiment 3 is that the nano material used in this embodiment is unmodified diamond.

[0107] Example 5

[0108] The difference between this embodiment and embodiment 3 is that the nanomaterials of this embodiment use a composite of modified nano-diamond and modified nano-copper, wherein the modified nano-copper adopts the modified nano-copper prepared in preparation example 2, and the weight ratio of the modified nano-diamond to the modified nano-copper is 1:1.2, specifically, the weight fraction of the modified nano-diamond is 2.73 parts, and the weight fraction of the modified nano-copper is 3.27 parts.

[0109] The specific preparation method comprises the following steps:

[0110] S1: Mix the poly-α-olefin base oil and the ester oil, heat to 50-60°C and maintain the temperature, and stir until the mixture is uniform;

[0111] S2: After lowering the temperature to 40-50°C, alkyl phosphite, dithiophosphate, modified nanodiamond and modified nanocopper are added in sequence, and stirring is continued for 2 hours to ensure that each component is fully dispersed;

[0112] S3: further cooling to 30-40°C, adding phenolic antioxidant, amine antioxidant and benzotriazole preservative in sequence, and stirring for 30 minutes;

[0113] S4: Raise the temperature to 50-60°C again, add fatty alcohol, polymethacrylate and viscosity index improver, and continue stirring for 1 hour;

[0114] S5: Cool naturally to room temperature to produce long-life anti-micropitting industrial gear oil.

[0115] Example 6

[0116] The difference between this embodiment and embodiment 5 is that the weight ratio of the modified nano-diamond and the modified nano-copper in this embodiment is different. In this embodiment, the weight ratio of the modified nano-diamond and the modified nano-copper is 1:1.3, specifically, the weight fraction of the modified nano-diamond is 2.61 parts, and the weight fraction of the modified nano-copper is 3.39 parts.

[0117] Example 7

[0118] The difference between this embodiment and embodiment 5 is that the weight ratio of the modified nano-diamond and the modified nano-copper in this embodiment is different. In this embodiment, the weight ratio of the modified nano-diamond and the modified nano-copper is 1:1.4, specifically, the weight fraction of the modified nano-diamond is 2.50 parts, and the weight fraction of the modified nano-copper is 3.50 parts.

[0119] Example 8

[0120] The difference between this embodiment and embodiment 5 is that the weight ratio of the modified nano-diamond and the modified nano-copper in this embodiment is different. In this embodiment, the weight ratio of the modified nano-diamond and the modified nano-copper is 1:1.3, specifically, the weight fraction of the modified nano-diamond is 2.40 parts, and the weight fraction of the modified nano-copper is 3.60 parts.

[0121] Example 9

[0122] The difference between this embodiment and embodiment 6 is that the nano-diamonds in the nano-material of this embodiment are not modified.

[0123] Example 10

[0124] The difference between this embodiment and embodiment 6 is that the modified nano-copper in this embodiment adopts the modified nano-copper prepared in preparation example 1.

[0125] Embodiment 11

[0126] The difference between this embodiment and embodiment 6 is that the modified nano-copper in this embodiment adopts the modified nano-copper prepared in preparation example 3.

[0127] Comparative Example 1

[0128] Commercially available industrial gear oil.

[0129] Comparative Example 2

[0130] The difference between this comparative example and Example 1 is that the formula of this comparative example does not include polymethacrylate, and an equal amount of poly-α-olefin base oil is used instead.

[0131] Comparative Example 3

[0132] The difference between this comparative example and Example 1 is that this comparative example uses an equal amount of unmodified nano-copper with the same particle size to replace the modified nano-diamond.

[0133] Comparative Example 4

[0134] The difference between this comparative example and Example 1 is that this comparative example uses an equal amount of nano copper oxide with the same particle size modified by Preparation Example 1 instead of modified nano diamond.

[0135] Comparative Example 5

[0136] The difference between this comparative example and Example 1 is that this comparative example uses an equal amount of nano-copper with the same particle size as that modified in Preparation Example 1 to replace the modified nano-diamond.

[0137] The performance of the industrial gear oils prepared in Examples 1 to 11 and Comparative Examples 1 to 5 was tested, and the test results are shown in Table 1.

[0138] Table 1 Performance test data of industrial gear oils of Examples 1 to 11 and Comparative Examples 1 to 5.

[0139]

[0140] (Continued from the above table)

[0141]

[0142]

[0143] The industrial gear oils prepared in Examples 5 to 9 passed the FZG micropitting resistance test (A / 8.3 / 90, test method according to DI NI SO 14635-1), and the test results showed that the load level was greater than level 14.

[0144] Passed FE-8 ball bearing wear test (D-7,5 / 80-80, test method according to DI N51777-2), test result: no wear.

[0145] Passed the Flender anti-foam test (ISO12152).

[0146] Passed the Filterability Test.

[0147] Passed the compatibility test for internal / external coatings used in Flender gear units.

[0148] Passed FVA54 VI I, 90℃ anti-micropitting test.

[0149] Combined with the above data, the industrial gear oil prepared by the present invention has many advantages such as low wear value, low friction coefficient, low water content, good anti-emulsification, good anti-rust performance and good anti-micropitting performance. Low wear value and low friction coefficient mean that during the operation of mining equipment, the friction and wear between gears will be greatly reduced, which can effectively extend the service life of the gears. Secondly, the industrial gear oil of the present invention has low water content and good anti-emulsification, which makes the gear oil less susceptible to the influence of moisture during use, maintains its stable performance, reduces micropitting or corrosion of parts, and further extends the service life of the gears.

[0150] In addition, the industrial gear oil also has good anti-rust performance and anti-micropitting performance. In mining equipment, due to the harsh working environment, gears are easily affected by corrosion and micropitting. The industrial gear oil prepared by the present invention can effectively prevent the occurrence of these problems, protect the gears from corrosion and micropitting, and thus extend the service life of the gears.

[0151] In summary, the industrial gear oil prepared by the present invention has excellent performance and long life characteristics when used in mining equipment. It can not only effectively extend the service life of the gear, but also improve the operating efficiency and stability of the mining equipment, and reduce maintenance costs and downtime.

[0152] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A long-life anti-micropitting industrial gear oil, calculated by weight, characterized in that: The components include: Poly-alpha-olefin base oil: 50-70 parts; Ester oil: 10-20 parts; Alkyl phosphite: 5-10 parts; Phosphorodithioate: 2-5 parts; Nanomaterials: 2 to 8 parts; Phenolic antioxidants: 1-3 parts; Amine antioxidant: 1-2 parts; Benzotriazole preservatives: 1-2 parts; Fatty alcohol: 1-3 parts; Polymethacrylate: 5-10 parts; Viscosity index improver: 2 to 5 parts.

2. A long-life anti-micropitting industrial gear oil according to claim 1, characterized in that: The nano material includes nano diamond, and the particle size of the nano diamond is 20-50 nm.

3. A long-life anti-micropitting industrial gear oil according to claim 2, characterized in that: The nano-diamond is nano-diamond modified by a silane coupling agent.

4. A long-life anti-micropitting industrial gear oil according to claim 2, characterized in that: The nano material also includes nano copper, and the weight ratio of the nano diamond to the nano copper is 1:1.2-1.

5.

5. A long-life anti-micropitting industrial gear oil according to claim 4, characterized in that: The nano copper is nano copper modified by organic quaternary ammonium salt.

6. A long-life anti-micropitting industrial gear oil according to claim 5, characterized in that: The organic quaternary ammonium salt is octadecyltrimethylammonium chloride.

7. A long-life anti-micropitting industrial gear oil according to claim 6, characterized in that: The modification method of nano copper comprises the following steps: Step 1: Accurately weigh appropriate amounts of Cu(NO3)2·3H2O and octadecyltrimethylammonium chloride, dissolve them in distilled water, and stir them thoroughly to form a uniform first solution and a second solution; Step 2: Add the first solution dropwise into the second solution, continue to stir thoroughly, and obtain a suspension; Step 3: After the suspension is loaded into the PPL liner, it is placed in a hydrothermal synthesis kettle made of stainless steel; the hydrothermal synthesis kettle is placed in an oven and heated to 95-105°C for 20-30 hours; Step 4: After the hydrothermal synthesis reactor is cooled naturally, the supernatant is removed, and the precipitate is washed with deionized water and anhydrous ethanol in turn, and ultrasonically treated, and then centrifuged to obtain a precipitate; Step 5: vacuum drying the precipitate at a temperature of 55-65° C. for 20-30 hours to obtain a powder; Step 6: calcine the above powder at 380-420° C. for 3-5 hours under N2 atmosphere to obtain modified nano copper.

8. A long-life anti-micropitting industrial gear oil according to claim 7, characterized in that: In the modification step, the mass ratio of the Cu(NO3)2·3H2O to the octadecyltrimethylammonium chloride is 1:1.8-2.

2.

9. A long-life anti-micropitting industrial gear oil according to claim 8, characterized in that: In the modification step, the mass ratio of the Cu(NO3)2·3H2O to the octadecyltrimethylammonium chloride is 1:

2.

10. A method for preparing a long-life anti-micropitting industrial gear oil, characterized in that: The following steps are involved: S1: Mix 50-70 parts of poly-α-olefin base oil and 10-20 parts of ester oil, heat to 50-60°C and maintain, stirring until the mixture is uniform; S2: After lowering the temperature to 40-50°C, 5-10 parts of alkyl phosphite, 2-5 parts of dithiophosphate and 2-8 parts of nanomaterial are added in sequence, and stirring is continued for 1-2 hours to ensure that the components are fully dispersed; S3: further cooling to 30-40°C, adding 1-3 parts of phenolic antioxidant, 1-2 parts of amine antioxidant and 1-2 parts of benzotriazole preservative in sequence, and stirring for 30 minutes; S4: Raise the temperature to 50-60°C again, add 1-3 parts of fatty alcohol, 5-10 parts of polymethacrylate and 2-5 parts of viscosity index improver, and continue stirring for 1 hour; S5: Cool naturally to room temperature to produce long-life anti-micropitting industrial gear oil.